Healthcare workers' experiences regarding scaling up of training on integrated disease surveillance and response (IDSR) in Uganda, 2016: cross sectional qualitative study - Lydia Nakiire; Ben Masiira; Christine Kihembo; Edson Katushabe; Nasan Natseri; Immaculate Nabukenya; Innocent Komakech; Issa Makumbi; Okot Charles; Francis Adatu; Miriam Nanyunja; Peter Nsubuga; et al. (BMC, 2019)
Abstract Background The Integrated Disease Surveillance and Response (IDSR) strategy was adopted as the framework for implementation of International Health Regulation (2005) in the African region of World Health Organisation (WHO AFRO). While earlier studies documented gains in performance of core IDSR functions, Uganda still faces challenges due to infectious diseases. IDSR revitalisation programme aimed to improve prevention, early detection, and prompt response to disease outbreaks. However, little is known about health worker's perception of the revitalised IDSR training. Methods We conducted focus group discussions of health workers who were trained between 2015 and 2016. Discussions on benefits, challenges and possible solutions for improvement of IDSR training were recorded, transcribed, translated and coded using grounded theory. Results In total, 22/26 FGDs were conducted. Participants cited improved completeness and timeliness of reporting, case detection and data analysis and better response to disease outbreaks as key achievements after the training. Programme challenges included an inadequate number of trained staff, funding, irregular supervision, high turnover of trained health workers, and lack of key logistics. Suggestions to improve IDSR included pre-service and community training, mentorship, regular supervision and improving funding at the district level. Conclusion Health workers perceived that scaling up revitalized IDSR training in Uganda improved public health surveillance. However, they acknowledge encountering challenges that hinder their performance after the training. Ministry of Health should have a mentorship plan, integrate IDSR training in pre-service curricula and advocate for funding IDSR activities to address some of the gaps highlighted in this study.